RESISTENSI RUANG PUBLIK DI TENGAH COVID-19 PERSPEKTIF ISLAM DAN KOMUNIKASI MULTIKULTURAL - Kurniawan, Andri; Yumna, Nibrasatul; Tantri, Erna (KOMUNIKE, 2020)
The public sphere in the midst of the Covid-19 pandemic experienced significant dynamics, because public sphere which is a shared property space as an arena for sharing public opinion is limited, especially in the Islamic view which emphasizes avoiding the plague. Moving away from the Covid-19 outbreak means staying away from the crowd as a form of priority to avoid danger. This study aims to describe public space in different circumstances amid a pandemic in an Islamic and multicultural perspective. The research method used is literature study through indepth analysis in parsing the problem in accordance with the term of research. The results of the research showed that public space in the middle of the Covid-19 pandemic experienced a shift in function to become a virtual public sphere. The phenomenon of public sphere in Islamic view and multicultural communication is normatively direct and threatening during the pandemic because it risks inviting a crowd so that many virtual-based spaces become active and effective spaces as dimensions of public sphere in the Covid-19 pandemic era.